Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan BIMBA AIUEO Cabang Jakarta Pusat: The Effect of Work Stress and Work Motivation on Employee Performance at BIMBA AIUEO’s Central Jakarta Branch - Mafikah Setianingsih; Desy Suryani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Prolonged work stress can reduce employee performance, increase errors, tardiness, and absenteeism, especially among teaching staff. This has a negative impact on the team and the company. Effective stress management is crucial to improving employee well-being and company performance. The purpose of this study is to examine the impact of Work Stress and Work Motivation on Employee Performance at biMBA AIUEO Central Jakarta Branch. The methodology used is descriptive quantitative and non-probability sampling, with saturated sampling, and a questionnaire was distributed to 84 employees of biMBA AIUEO Central Jakarta Branch. The study results show that the F value of 57.088 < F table 3.10, thus it is stated that work stress and work motivation have a positive and significant effect simultaneously on employee performance. Partially, work stress obtained a t value of 4.768 > t table 1.989, which means H01 is rejected, and work motivation obtained a t value of 10.685 > t table 1.989, so H01 is rejected.